Exacerbated High‐Temperature Calendar Aging of SiOx‐Graphite Electrode Induced by Interparticle Lithium Crosstalk - Zhang, Yu; Wen‐Peng Wang; Zhao, Yao; Zhang, Xing; Guo, Hua; Gao, Hongcai; Di‐Xin Xu; Yu‐Ming Zhao; Li, Ge; Jia‐Yan Liang; Sen, Xin; Yu‐Guo Guo (Advanced functional materials, 2024)
Silicon oxide‐graphite (SiOx‐G) composites are promising anode materials for building practical high‐energy Li‐ion batteries. To acquire long and safe operation of battery, extensive efforts are made to maintain stable Li storage of SiOx‐G against materials aging and the accompanied performance fade. While previous studies mostly focus on the cycling aging, the calendar aging occurred during battery storage at a high state of charge or high temperature has not received sufficient attention. In this work, a mechanism study on the calendar aging chemistry of fully lithiated SiOx‐G electrodes in half‐cells both at ambient and high temperature (60 °C) is performed. Unmodified SiOx is employed as active materials to inspect the change of thermodynamics properties in the bulk and at interfaces. By excluding the interference from cathode, it is revealed that besides aggravated parasitic reactions happening at interface, Li migration from the lithiated graphite to the vicinal SiOx particles is also responsible for calendar aging of SiOx‐G electrodes, and high‐temperature storage notably accelerates the aging process. This work enriches the fundamental understandings about the multifactor‐coupled aging process of anode materials and sheds lights on rational materials design toward improved calendar life of a high‐energy rechargeable battery.